Pengaruh Service Quality Dan Customer Satisfaction Terhadap Repurchase Intention Pada Restaurant Pochajjang Bogor Di Masa Pasca Pandemi Covid-19 - Feoline Berliana; Mashadi Mashadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The development of culinary food in Indonesia has also resulted in a large participation in national economic growth. The purpose of this study was to determine the effect of employee service quality on repurchase intentions at Pochajjang Bogor restaurants in the post-Covid-19 pandemic, to determine the effect of customer satisfaction on repurchase intentions at Pochajjang Bogor restaurants in the post Covid-19 pandemic, and to find out whether service Quality and customer satisfaction can jointly influence repurchase intention at Pochajjang Bogor restaurant in the post covid-19 pandemic. The sampling method used is non-probability sampling from the formula Hair et al. From this formula the authors set a sample of 120, but when running data processing requires additional data of 41, the total sample in this study is 161. Based on the test results, the results obtained are that : (1) Service quality has a positive and partially significant effect on repurchase intention, (2) Customer satisfaction has a partially positive and significant effect on repurchase intention, (3) Service quality and customer satisfaction together the same has an effect on repurchase intention, but the magnitude of the influence of the variable Service Quality and Customer Satisfaction on Repurchase Intention is only 0.268 or 26.8%. Therefore, Pochajjang Bogor restaurant employees must continue to improve the quality of their services and monitor customer expectations and try to fulfill them so that customers are always satisfied. Key Words : Service Quality, Customer Satisfaction, Repurchase Intention.